2013
DOI: 10.1099/mic.0.061879-0
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the NFκ-B signal transduction pathway in response to Corynebacterium diphtheriae infection

Abstract: Corynebacterium diphtheriae, the causative agent of diphtheria, has been thoroughly studied with respect to toxin production and pili formation, while knowledge on host responses to C. diphtheriae infection is limited. In this study, we studied adhesion to and invasion of epithelial cells by different C. diphtheriae isolates. When NFk-B reporter cell lines were used to monitor the effect of C. diphtheriae infection on human cells, strain-specific differences were observed. While adhesion to host cells had no e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1
1

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Compared with adhesion rates found for different C. diphtheriae strains (for review, see Ott & Burkovski, 2014) and invasion rates determined (e.g. Ott et al, 2013), C. ulcerans rates observed here were at least two-to fivefold higher, indicating the high infectious potential of this pathogen. This is further supported by detrimental effects on epithelial cells as shown by the breakdown of transepithelial resistance of cell monolayers after infection with C. ulcerans BR-AD22 and 809.…”
Section: Discussionmentioning
confidence: 94%
“…Compared with adhesion rates found for different C. diphtheriae strains (for review, see Ott & Burkovski, 2014) and invasion rates determined (e.g. Ott et al, 2013), C. ulcerans rates observed here were at least two-to fivefold higher, indicating the high infectious potential of this pathogen. This is further supported by detrimental effects on epithelial cells as shown by the breakdown of transepithelial resistance of cell monolayers after infection with C. ulcerans BR-AD22 and 809.…”
Section: Discussionmentioning
confidence: 94%
“…Strain DSM43989 is a PW8 strain used for toxoid production. In previous studies, DSM43989 showed low adhesion to and invasion into epithelial cells in comparison to other non-toxigenic isolates [21] and we were interested to elucidate the reason for this behavior. The number and types of surface pili are important for adhesion and invasion [19,23,24]; however, their presence has been verified by atomic force microscopy [19,23].…”
Section: Introductionmentioning
confidence: 99%
“…The ability of Cor. diphtheriae to enter cultured respiratory epithelial cells was first shown by Hirata et al (2002) and validated by a number of further studies (Mattos-Guaraldi, 2002;Bertuccini et al, 2004;Ott et al, 2010aOtt et al, , b, 2013.…”
Section: Introductionmentioning
confidence: 99%